2021
DOI: 10.1123/jpah.2020-0540
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Neighborhood Park Use Is Associated With Physical Activity Among Adults in Four US Cities

Abstract: Background: Neighborhood parks are recognized as important spaces for facilitating physical activity (PA); however, it remains unclear how the frequency of park use is associated with PA. The purpose of this study was to examine associations between minutes of moderate to vigorous PA and multiple park use indicators: (1) use of a neighborhood park, (2) unique number of neighborhood parks used, and (3) frequency of neighborhood park use. Methods: Adults were surveyed from 4 US cities (Brooklyn, NY; Greenville C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Intentionally interacting with nature is not only associated with health outcomes but also health behaviors, especially engagement in physical activity [ 49 , 113 , 207 , 219 , 243 , 244 , 245 , 246 ]. For example, greater frequency of intentional interactions has been associated with meeting physical activity guidelines [ 190 , 247 , 248 ], more steps taken per day [ 249 ], and engagement in moderate-to-vigorous physical activity [ 250 ]. Greater durations of intentional interactions with nature have been associated with engagement in physical activity [ 133 ] and moderate-to-vigorous physical activity [ 251 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intentionally interacting with nature is not only associated with health outcomes but also health behaviors, especially engagement in physical activity [ 49 , 113 , 207 , 219 , 243 , 244 , 245 , 246 ]. For example, greater frequency of intentional interactions has been associated with meeting physical activity guidelines [ 190 , 247 , 248 ], more steps taken per day [ 249 ], and engagement in moderate-to-vigorous physical activity [ 250 ]. Greater durations of intentional interactions with nature have been associated with engagement in physical activity [ 133 ] and moderate-to-vigorous physical activity [ 251 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 13 studies that used PPGIS methods that focused on urban green spaces (Bijker & Sijtsma, 2017; Brown et al, 2014, 2018; de Vries et al, 2013; Heikinheimo et al, 2020; Hughey et al, 2021; Korpilo et al, 2021; Latinopoulos, 2022; Pietrzyk‐Kaszyńska et al, 2017; Rall et al, 2019; Ramírez Aranda et al, 2021; Raymond et al, 2016; Schrammeijer et al, 2022). Nine studies explicitly asked participants to identify and map the green spaces they used.…”
Section: Approaches To Measuring Park Usementioning
confidence: 99%
“…Nine studies explicitly asked participants to identify and map the green spaces they used. However, the specific instructions and recall periods differed across all studies (for example, “visit most” [Schrammeijer et al, 2022], “spend the most time in” [Latinopoulos, 2022], “used in the past 30 days” [Hughey et al, 2021], “frequently visit” [Korpilo et al, 2021], “used for activities in the past two weeks,” “places where you spend time within green spaces” [Pietrzyk‐Kaszyńska et al, 2017], and “areas you enjoy using” [Raymond et al, 2016]). The remaining four studies were less explicit in their instructions, asking participants to map green spaces that were their “favourite” (Raymond et al, 2016), “meaningful” (Rall et al, 2019), or “attractive, valuable or important” (Bijker & Sijtsma, 2017; de Vries et al, 2013).…”
Section: Approaches To Measuring Park Usementioning
confidence: 99%
See 1 more Smart Citation
“…Parks and greenspace improve physical health in many ways, often by creating environments that encourage active lifestyles and improve access to exercise opportunities [8]. Studies have shown that park availability and park use are positively correlated with physical activity [9]. Use of greenspace and outdoor recreation can also enhance cardiovascular health by influencing risk factors such as cholesterol levels, hypertension, BMI, and obesity [10].…”
Section: Physical Health Benefitsmentioning
confidence: 99%